Ecologias informacionais complexas em centros de referência LGBTQIA+ no Brasil - Silva, Laelson Felipe da (2023)
The study presents the informational environments of LGBTQIA+ Human Rights Reference Centers in Brazil. It considers the context of development of public policies targeting marginalized groups in the country, taking into account their deinstitutionalization process. Problematising the constitution of physical and digital environments of LGBTQIA+ Human Rights Reference Centers, based on the theoretical-conceptual elements of Information Architecture in its informational approach, in light of the continuous transformations of information and communication technologies. It demonstrates its relevance by introducing reflections on a problem/object that is still underexplored from the perspective of Information Architecture in the field of Information Science. It is inferred that if implemented, the elements of informational architecture have the potential to generate applications that will expand the reach of services offered by LGBTQIA+ Human Rights Reference Centers. It raises the question: How to model complex informational ecologies for LGBTQIA+ Reference Centers in Brazil using Information Architecture? The objective is to develop a model for the development of a complex informational ecology for LGBTQIA+ Human Rights Reference Centers. The study considers the population to be the 38 centers whose existence was confirmed during the research survey stage. The sample, non-probabilistic in nature, selected based on accessibility and typicality criteria, corresponds to 14 centers. The quadripolar method is used to guide the investigative path given its flexibility and adaptability in analyzing problems/objects constituted from the Social Sciences. The study is characterized by a qualiquantitative approach, applied in nature, and has exploratory and propositional objectives. It employs a combination of bibliographic, documentary, and field research as its research instruments. The data collection instrument used is the questionnaire. The analysis employs the Methodological Essay for Pervasive Information Architecture adapted to the Informational Approach, as well as the Checklist of Information Architecture Elements for Hybrid Environments. The results include the map of existing centers in Brazil, the essential elements of the centers, a model of the physical environment, and a model of the digital environment. The study concludes that the incorporation of government programs at the core of federal units as State policies enhances the spread of reference centers; the centers possess essential elements that characterize them and can be taken as a starting point for the construction of physical and digital environments; it is not necessarily required to have a physical unit in operation for the centers to continue offering some of their services. Based on Information Architecture, from both theoretical and pragmatic perspectives, LGBTQIA+ Human Rights Reference Centers have the potential to develop as Complex Informational Ecologies, but they require architectural models and guidelines that assist them in achieving the full potential offered by available technologies.